2008
DOI: 10.1088/0022-3727/41/17/175213
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of alternative propellants for the helicon double layer thruster

Abstract: Ion energy distribution functions are measured using a retarding field energy analyser located 7.5 cm downstream of a helicon double layer plasma source, respectively, operating with four molecular gases: nitrogen (N 2), methane (CH 4), ammonia (NH 3) and nitrous oxide (N 2 O). For radiofrequency powers of a few hundred watts, and a magnetic field diverging from about 0.013 T (130 G) in the source to about 0.001 T (10 G) in the exhaust, an ion beam is detected for each propellant over a very similar operating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…The lifetime of the HDLT is not limited by grid erosion mechanisms and the thruster produces a quasi neutral plume, therefore a hollow cathode or alternative beam neuralising device is made redundant. Proof of concept and thruster functionality has been demonstrated for a variety of propellants, magnetic field topologies and source tube dimensions [3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The lifetime of the HDLT is not limited by grid erosion mechanisms and the thruster produces a quasi neutral plume, therefore a hollow cathode or alternative beam neuralising device is made redundant. Proof of concept and thruster functionality has been demonstrated for a variety of propellants, magnetic field topologies and source tube dimensions [3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The resultant ion acceleration to supersonic speeds and the characteristic high ion densities of helicon discharges motivated researchers from the Australian National University ͑ANU͒ to propose the helicon double layer thruster ͑HDLT͒ concept. 2 Although the specific impulse and thrust of the HDTL are low compared to conventional thrusters, the possibility of electrically steering the ejected ion beam, 3 stable operation at very low pressure in a variety of gases, 4 and the possibility of high energy efficiency 5 are sufficiently intriguing that HDLT optimization studies have continued. For example, recent studies have shown that the overall energy efficiency can be significantly improved by replacing the heavy solenoids used to generate the axial magnetic fields with smaller and lighter permanent magnets.…”
mentioning
confidence: 99%
“…nitrogen, nitrous oxide, oxygen and carbon dioxide (Charles, 2004;Charles et al, 2006Charles et al, , 2008bCharles, 2009;Charles et al, 2009).…”
Section: Recent Experimental Workmentioning
confidence: 99%